A study on the Singapore labour force : structure and manpower development - Lee, Paul Ark Eng (2015)
This Final Year Project is prepared in partial fulfillment for the degree of Bachelor of Business. The major purpose of this study is to analyse the current trends of the Singapore labour force and the relevant issues that will impact Singapore's competitive strength in the international arena. We will discuss how the government's economic development strategies have shaped the changes in the industrial and occupational structure. In addition, the Strategic Economic Plan pursued by Singapore recently has certain critical implications for the future development of labour force that will be discussed in this study. In particular, it is necessary to upgrade and equip the Singapore labour force with the skills desired by the foreign investors through intensive education and training. As the Singapore economy continues to expand and diversify, it is imminent that a large pool of workers are needed in all industrial sectors. However, the labour shortage is placing an obstacle to its advancement efforts. The relatively untapped source of female labour, as presented in this study, will serve to alleviate some degree of the labour crunch. From there, we will bring in the viable part-time work options that will help to attract more economically inactive persons into the labour force. In this study, we depict the fact that highly-skilled foreign labour will play a critical role in the process of regionalisation and globalisation. Finally, we will highlight the current standing of the Singapore labour force with an evaluation tool known as Quality of Workforce Index (QWI), as against its major economic competitors.